Adoption of Improved Sugarcane Production Technologies - Singh, D.K.; Itawadiya, Kamalesh; Singh, P.K. (Indian Journal of Extension Education, 2012)
India ranks first among sugarcane growing countries in the world, both in area and production. The crop occupies an area  of 1,800 ha. with an average production of 7,800 tonnes and productivity is 4.33 t/ha in Sehore district of Madhya Pradesh.  The challenge is to enhance the productivity of sugarcane from existing 75 tonnes/ha to 100 tonnes/ha by 2020 AD. There  is a wide gap between the standardized well tested production systems and practices followed by the farmers. The study  was conducted in Sehore district, Madhya Pradesh .The data were collected by interviewing 90 farmers selected on the  basis of proportionate random sampling from six villages of Sehore Block of Sehore district. It was found that majority of  respondents had medium levels of technological adoption. The study is significant for sugarcane production technologies,  so that appropriate strategies can be designed for specific segment of the farming community.
Keywords: Extent of adoption; improved production technology; weed-control measures